Judes-Èdip en l'edat mitjana. - VILARDELL, ALBERT TOLDRÀ I. (Scripta)
A medieval legend joins two literary characters: the Judas from gospels and the classical Oedipus from the Sophocles tragedy; we find so a Judas that, in addition to the sins that we already know (treason, avarice, lie, satanism, suicide etc.), commits two "oedipical" transgressions: parricide -he kills his father- and incest -he marries his mother. In this article we follow the textual tradition of this fussion, from XIIth century to XVIth, particularly over the occitan and catalan theatrical "passions", the Varazze's Legenda aurea and some references from saint Vincent Ferrier and Francesc Eiximenis.